Pengaruh Komunikasi Efektif Orangtua terhadap Perilaku Anak Usia Dini di Desa Kelapapati Tengah Kec. Bengkalis - Jingga Khaila Rorenza; Mufaro'ah Mufaro'ah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research is titled "The Influence of Parental Communication on Children's Behavior in Kelapapatí Tengah Village, Bengkalis District". The aim is to get an overview of parent-child communication, identify factors hindering communication, and the extent to which parental communication affects children's behavior. This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. The results showed that: (1) Parent-child communication in Kelapapatí Village sometimes goes well, but there are still some that are not good, causing concern and influencing children's behavior outside the home; (2) Factors hindering communication are job demands (career) and the economy; (3) The influence of parental communication on children's behavior can be seen from changes in children's attitudes at home and school, such as lack of respect for teachers and parents, frequent quarrels with friends, often using harsh words, and others. This will have an impact on children's development in the future.